(untitled) (Journal of Enam Medical College, 2014)
Background: Infection with Helicobacter pylori (H. pylori) is a recognized cause of peptic ulcer and gastritis. Persistence of infection is a definite risk factor for gastric malignancy. Healing of gastritis after eradication of H. pylori reduces the risks of peptic ulcer disease and gastric malignancy. Objectives: To find out the relationship of H. pylori with erosive and nonerosive gastritis, the effect of anti-H. pylori therapy and to compare the effects of anti-H. pylori therapy between two types of gastritis. Materials and Methods: This prospective study was done in the Gastroenterology department of Bangabandhu Sheikh Mujib Medical University, Dhaka from June 2008 to May 2009. One hundred eighty dyspeptic patients were enrolled for the study. Patients with gastritis diagnosed by endoscopy underwent rapid urease test (RUT). RUT positive patients were considered to have H. pylori infection and were treated with triple therapy (omeprazole, amoxycillin and metronidiazole) for 14 days. Treatment responses were assessed by clinical history and also by endoscopic biopsy and RUT. Results of endoscopic findings and RUT after treatment were compared with pretreatment status. Results: Seventy patients completed the treatment and finally could be assessed. Endoscopic findings of 70 patients revealed that 56 (80%) patients had erosive gastritis and 14 (20%) patients had nonerosive gastritis. After treatment, 47 (67.1%) lesions became normal, 16 (22.9%) remained erosive and 7 (10%) non-erosive as before. Out of 14 non-erosive diseases, 7 became normal, while out of 56 erosive diseases 40 became normal. The erosive group responded significantly better than the non-erosive group (c2=32.766, p<0.001). Fifty nine (84.3%) patients with gastritis showed negative urease test after treatment. Conclusion: Strong relation between H. pylori infection and gastritis was found. Majority were antral erosive gastritis. Erosive group responded better than non-erosive group. DOI: http://dx.doi.org/10.3329/jemc.v4i1.18063 J Enam Med Col 2014; 4(1): 15-20